Does Individualism and Uncertainty Predict Operational Discipline in Brazilian Oil and Gas Industry? - Lafraia, João; Dias, Murillo (European Journal of Applied Sciences, 2024)
This study examines the impact of organizational power distance, uncertainty avoidance, autonomy, and trust on the capacity to produce desired operational discipline and achieve better ESG results in a Brazilian Oil and Gas Company's business unit. Previous studies highlight the importance of intangible factors in internal coordination for operational discipline. However, a combination of low trust, high power distance, high uncertainty avoidance, and collectivism creates a reactive planning culture, increasing transaction costs and hindering efficiency and effectiveness in solving complex problems. The results show that individualism and uncertainty avoidance predict operational discipline, while power distance and trust moderate the first two variables.